The influence of attitude toward behavior and social media on customer intention on the SeaBank application - Nazifah Aini; Husnil Khatimah (Trigin Publisher, 2026)
This study examines how behavioral attitudes and social media shape customers’ intentions to adopt SeaBank digital banking service. Rapid fintech growth has pushed banks to enchance digital offerings and attract broadr user bases. Using quatitative methods, data come from 48 respondents via structured questionnaire and the sampling technique used in this study was purposive sampling. Data was conducted using the PLS-SEM revealed that behavioral attitudes significantly boost customer intentions, while social media shows a positive but non-significant impact. The model accounts for 38.8% of intention variance, highlighting attitudes as the dominant driver over social media in digital banking uptake.